Synthetic Approaches to Star‐Shaped Molecules with 1, 3, 5‐Trisubstituted Aromatic Cores. Issue 9 (29th March 2019) - Kotha, Sambasivarao; Meshram, Milind; Panguluri, Nageswara Rao; Shah, Vrajesh R.; Todeti, Saidulu; Shirbhate, Mukesh E.
Abstract: Herein, we summarize the synthetic approaches that have been developed for the synthesis of star‐shaped molecules. Typically, to design such highly functionalized molecules, simple building blocks are first assembled through trimerization reactions, starting from commercially available starting materials. Then, these building blocks are synthetically manipulated to generate extended star‐shaped molecules. We also discuss the syntheses of star‐shaped molecules that contain 2, 4, 6‐trisubstituted 1, 3, 5‐triazine or 1, 3, 5‐trisubstituted benzene rings as a central core and diverse substituted styrene, phenyl, and fluorene derivatives at their periphery, which endows these molecules with extended conjugation. A variety of metal‐catalyzed reactions, such as Suzuki, Buchwald–Hartwig, Sonogashira, Heck, and Negishi cross‐coupling reactions, as well as metathesis, have been employed to functionalize a range of star‐shaped molecules. The methods described herein will be helpful for designing a wide range of intricate compounds that are highly valuable in the fields of supramolecular chemistry and materials science. Owing to space limitations, we will not cover all of the publications on this topic. Instead, we will focus on examples that were reported by our research group and other relevant recent literature. Apart from the trimerization sequence, this Minireview has been structured based on the key reactions that were used to prepare the star‐shaped molecules and other higher analogues. Finally, some examples that do not fit into this classification are discussed. Abstract : Star Trek : This Minireview summarizes the methods that have been used for the synthesis of star‐shaped molecules. Popular cross‐coupling reactions, such as Suzuki, Buchwald–Hartwig, Heck, and Negishi cross‐coupling reactions, as well as metathesis, have all been used for this purpose, whilst the van Leusen oxazole synthesis has also been employed to assemble star‐shaped oxazoles.